MENTAL HEALTH LITERACY, INTENTION OF PSYCHOLOGICAL SYMPTOMS AT PUBLIC SCHOOL 11 LANGKAI - Isa Andreyanku Lana; Frisca Reggina, Restiani, Lydia, Ausvina, Dandi, Yola Pradita (Jurnal Kesehatan, 2024)
This research explores the understanding and response to the mental health of children at the Langkai 11 Public Elementary School, especially those aged 10-11 years. The focus is on how the basic educational environment influences the foundations of children's mental health. Through a method involving three experienced teachers as the main resource persons, this research used a purposive sampling approach and structured interviews. Data analysis highlights the importance of managing children's emotions as key to supporting their psychological well-being. The diverse emotional responses emphasize the need for appropriate approaches in managing children's emotions. The definition of mental health literacy adopted by educators focuses on a comprehensive understanding of children's physical and mental well- being by paying attention to positive behavioral aspects. The conclusions of this research underscore the importance of understanding mental health literacy in primary education settings as well as the need for strategies that support children's mental health. The implication is that an emphasis on managing children's emotions and appropriate responses is the main key in creating an educational environment that supports holistic mental health.